2002
DOI: 10.3102/00028312039004943
|View full text |Cite
|
Sign up to set email alerts
|

Short Circuits or Superconductors? Effects of Group Composition on High-Achieving Students’ Science Assessment Performance

Abstract: Although many cooperative learning methods advocate grouping students heterogeneously in order to maximize the diversity of perspectives, skills, and backgrounds, past research shows that heterogeneous grouping generally benefits low-ability students but does not necessarily benefit high-ability students. This study investigates the effects of group ability composition (homogeneous versus heterogeneous) on group processes and outcomes for high-ability students completing science performance assessments. High-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 53 publications
7
70
1
3
Order By: Relevance
“…published by Webb and colleagues (Webb, Nemer, & Zuniga, 2002), this finding was called into question, as she reported that high-achievers tended to do well when grouped together homogeneously, and sometimes did well when grouped with low-achievers.…”
Section: Ideas and Identities 26mentioning
confidence: 99%
See 1 more Smart Citation
“…published by Webb and colleagues (Webb, Nemer, & Zuniga, 2002), this finding was called into question, as she reported that high-achievers tended to do well when grouped together homogeneously, and sometimes did well when grouped with low-achievers.…”
Section: Ideas and Identities 26mentioning
confidence: 99%
“…It is important that the teacher name an academic contribution (e.g., "your idea is really important and your group should think about that"), rather than simply a social or behavioral one (e.g., "you're sitting nice and quietly") to encourage other students to recognize the marginalized student's competence. The central participation of lower-status students in a group actually benefits the whole group, who then have the opportunity to compare identities, correct errors, and come to a deeper understanding of mathematical concepts (Webb, Nemer, & Zuniga, 2002). …”
Section: Ideas and Identities 36mentioning
confidence: 99%
“…The Sobel test however, showed that the indirect effect was significant, Z = 2.043, p = .041, meaning that awareness of participation can be considered a partial mediator for student participation in the chat discussions (e.g., asking for elaborated help and giving elaborated explanations, see Webb, Nemer, & Zuniga, 2002). The percentage of the total effect of overall duration of PT use on student participation that is mediated by awareness of participation is 20.73% (e.g., prior knowledge, achievement motivation, see Dillenbourg, Baker, Blaye, & O'Malley, 1996).…”
Section: -------------------------------------------------Insert Figumentioning
confidence: 99%
“…This is problematic because such an approach does not explain why in some groups the interaction between group members contains high levels of reasoning and collective thinking resulting in learning gains for all students, while in other groups-although they were assigned the same task-the quality of group members' interaction and learning is disappointing (Barron 2003;Hogan et al 1999;Webb et al 2002). A possible explanation is that these results might be due to factors such as group composition and students' prior knowledge and social skills.…”
Section: Process-oriented Collaborative Learning Research: Advantagesmentioning
confidence: 59%
“…The first example concerns studies that focus on the process of giving and receiving explanations that occurs during collaborative learning. This process has been extensively studied by Webb and her colleagues (cf., Webb 1989;Webb and Farivar 1999;Webb and Mastergeorge 2003;Webb et al 2002;Webb et al 1995). This line of research demonstrated that giving elaborate explanations (i.e., an explanation that contains a reason why the problem should be solved in a certain way) correlates positively with student achievement, whereas giving explanations without an elaboration (i.e., telling someone the answer without giving a clarification) does not (Webb 1991).…”
Section: Process-oriented Collaborative Learning Research: Advantagesmentioning
confidence: 97%